WEAVING MEMORIES AND ABSENCES: SELF-BIOGRAPHY AS ART’S MATERIAL (Palíndromo, 2018)
This article searched for the com-prehension of self-biography as art’s material. The reference artists were Louise Bourgeois, Frida Kahlo and José Leonilson. Bourgeois transforms her memories, loses and traumas in art. Kahlo mislead the pain, expresses her passion for life. Leonilson faces the proximity of death. I’ve found connections with those artists whose lives and works gets mixed. The methodological procedure comes from theoretical investigation and from practical work in relation with the dialectic during the whole process. From Gaston Bachelard, concern the concept of house/body, as place of the dreamlike dimension of memory. Philippe Lejeune discusses self-biography and the writing diary with the function of preser-ving memory. Georges Didi-Huberman talks about the absence as presence, trace, and the skin as place of signs of both aging/memory and of desire/touch. The result of this process were three works that connect with the artists listed and with the concepts brought by the theorists, and show the use of memory, self-biography and the absen-ces as singular expressions.
Keywords: memories; absences; self-biography; art